The neutron sensitivities of Geiger-Müller counters - Jones, D T L (Division of Medical Physics, 2017)
Neutron beams are always accompanied by gamma rays. Because neutrons and gamma rays have different biological effects, it is essential that the neutron and gamma dose components be determined when neutron beams are used for radiotherapy and radiobiology. Since gamma ray dosimeters almost always also respond to neutrons, it is generally not possible to use two different devices to measure the separate dose components. The separate doses are usually determined by making measurements with two instruments which have different sensitivities to the two types of radiation and deducing the separate components from these measurements. One instrument usually has approximately equal sensitivity to both neutrons and gamma rays while the other has a low sensitivity to neutrons. The latter instrument is often a Geiger-Müller (G-M) counter. Although its neutron sensitivity (kᵤ) is low, it must be measured for accurate dose determinations. Previous u measurements of the neutron sensitivities of such counters have not always been in good agreement. In the present work the neutron sensitivities of two types of G-M counters, viz. ZP1320 and ZP1300 have been measured at neutron energies between 0.72 and 7.42 MeV. An absolute measurement of the neutron sensitivity of the ZP1320 counter was made at 3 MeV using the associated particle technique while the neutron sensitivities of both counters were measured at several energies using the pulsed beam time-of-flight technique. For the latter measurements a NE213 scintillation counter was used to measure the neutron flux. The detection efficiencies of this counter were calculated and the validity of the calculations were confirmed by measurements using the associated particle technique. The neutron sensitivities obtained in the present work are in reasonable agreement with most previous measurements. All available data for similar types of counters were fitted with a function of the form kᵤ(E) = a Eᵇ. The values of the fitting parameters were ZP1320 (0.72 to 7.42 MeV) : a = 0.10 ± 0.01, b = 1.32 ± 0.05 and ZP1300 (0.57 to 15.65 MeV) a = 0.25 ± 0.01, b = 1.32 -+ 0.05 b = 0.78 ± 0.03.